Transformasi Peran Ulama dalam Pergerakan Politik - Haniah Hanafie (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
Ulama or kiai is often understood as a religious authority. However, in its development, ulama is not only seen as a guide in practicing religious teachings but also in all aspects of life, so that all behaviors and actions of ulama will be imitated without reserve. Even their followers (jamaah) tend to justify or protect them when the ulama face challenges from other parties. The role of ulama known so far only as preachers, lecturers, caretakers of Islamic boarding schools, and religious leaders, turns out to be not like that, because history proves that ulama also play a role in practical politics. This article attempts to revisit the role played by ulama in the political arena, both during the Dutch Colonial, Japanese, and Independence periods, especially during the New Order era, where the role of ulama underwent changes. Ulama were returned to their purely religious role.